THE APPLICATION OF CONTEXTUAL TEACHING AND LEARNING APPROACH (CTL) TO ENHANCE THE STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT - Tamala Yusuf, Rian Sesar; Muin, Abdul; Baso, Farisha Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The objective of the research was to find out the improvement of the students achievement in writing ability especially in writing descriptive text through Contextual Teaching and Learning Approach (CTL) in term of content and organization. The researcher used Classroom Action Research (CAR). This action research study consisted of two cycles. The population of this research is the second grade students of SMA Muhammadiyah 2 Makassar in the academic year 2017/2018. The sample of this research is the students in class XI IPS, the total number students of this class is 30 students, consists of 18 female and 12 male. The data of this study were qualitative and quantitative. The qualitative data were obtained by observing the teaching and learning process during the implementation of the actions by using field notes. And quantitative were obtained by giving tests to the students. The results of the research indicated that the used of Contextual Teaching and Learning Approach (CTL) improved the students’ ability in writing descriptive text. The total mean score of the students’ ability in writing descriptive text covering content and organization in diagnostic test was 57.23, cycle I was 68.66 and cycle II was 79.66, it improved 39.19%. Based on the result, it concluded that the use of Contextual Teaching and Learning Approach (CTL) was able to improve the students’ ability in writing descriptive text and also improved interest, motivation, and attitudes toward the teaching and learning process.